Do you mean silver sulfite or silver sulfide. I will assume you mean what you wrote. Nothing will change, except the formula, if it is Ag2S.
Ag2SO3 ==> 2Ag^+ + SO3=
Ksp = (Ag^+)^2(SO3^=)
(Ag^+) = 3.6 x 10^-4 from the problem.
(SO3^=) = 1/2 that.
Plug into the Ksp expression and calculate Ksp.
Im really sorry I got sidetracked:P This is the question I wanted to ask you
In a saturated solution of silver sulfite, the concentration of silver ion is 3.6 x 10^-4 mol/L. The Ksp of silver sulfite willl be what?
Sorry about that
5 answers
Ksp = [SO3][Ag]^2 / [Ag2SO3]
= [1.8 x 10^-4][3.6 x 10^-4]^2 /
[ ]
Would I divide by 1.8 x 10^-4 since there is one mole of Ag2So3?
= [1.8 x 10^-4][3.6 x 10^-4]^2 /
[ ]
Would I divide by 1.8 x 10^-4 since there is one mole of Ag2So3?
Ksp = (Ag^+)^2(SOc^=).
The denominator is 1, not (Ag2SO3).
This is not an equilibrium constant. No Ksp has anything on the bottom except 1.
The denominator is 1, not (Ag2SO3).
This is not an equilibrium constant. No Ksp has anything on the bottom except 1.
AHHH help i have no idea!!!
KSP for Au2 S